The Effect of Service Marketing Mix and Service Quality on Student Satisfaction at Indonesian High School of Management Sciences Banjarmasin - Afiannor Alfiannor (PT. Hanken SUkses Jaya, 2022)
This study aims to test empirically and analyze the effect of the Service Marketing Mix and Service Quality on Student Satisfaction at Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin. Research Methods, following the research objectives that have been formulated, this study uses a level of explanation, namely research that aims to explain the position of the factors studied and the relationship between one factor and another. (Sugiyono, 2002). Thus this study explains the effect of Marketing Mix and Service Quality on Student Satisfaction Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin. The research sample was 131 respondents with a sampling technique using the Slovin formula and analyzed with Multiple Regression Analysis using analysis tools SPSS 25.0 for Windows. The results of the research, service marketing mix variables and service quality simultaneously have a significant effect on student satisfaction at ltan berpengaruh signifikansi terhadap kepuasan mahasiswa pada Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin. Service marketing mix with product elements, price place promotion people physical evidence and process partially affect student satisfaction at Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin. Service quality with elements with the dimensions Tangible, Reliability, Responsiveness, Assurance, and Empathy affects student satisfaction in Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin. Service quality is more dominant than the service marketing mix. So, it can be concluded that the better the quality of service that is implemented or provided by Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin maka semakin meningkatkan kepuasan Mahasiswa.